Changes in mechanical load and extensor muscle activity in the cervico-thoracic spine induced by sitting posture modification - Edmondston, Stephen; Sharp, M.; Symes, A.; Alhabib, N.; Allison, Garry (Taylor & Francis Ltd., 2011)
The influence of whole body sitting posture on cervico-thoracic posture, mechanical load and extensor muscle activity was examined in 23 asymptomatic adults. Cervical and upper thoracic extensor muscle activity measured in guided slouched and lumbo-pelvic neutral postures was normalised to that measured in a self-selected habitual posture. Head and neck posture and gravitational load moment measurements were obtained in each posture. Sagittal head translation, upper cervical extension and load moment were significantly greater in the slouched posture (p < 0.001). Contrasting patterns of cervical and thoracic extensor activity were observed in the slouched and neutral postures, with cervical extensor activity 40% higher in the slouched posture (p < 0.0001). Thoracic extensor activity was significantly higher in the lumbo-pelvic neutral posture than the habitual posture (p = 0.002). The significant changes in extensor muscle activity with postural modification appear to be induced by the associated change in mechanical load moment of the head.